A simple practical patient-reported clinic satisfaction measure for young adults - Phillips, R (Nature Publishing Group, 2010)
BACKGROUND: The development of practical patient-reported outcome measures (PROM) to assess the user view of health programmes is increasingly important. Valid, shorter instruments are more likely to be used and completed than extensive questionnaires. METHODS: Consecutive adult outpatient attendees who were long-term survivors of childhood cancer completed the 16-item Patient Satisfaction with Communication Questionnaire (PSCQ). These data were used to develop a three-item questionnaire. The brief PROM was validated against data from a second, independent survey conducted in a similar fashion. RESULTS: In all, 93 individuals contributed PSCQ data, a response rate of 63%. The brief PROM was highly correlated with the original PSCQ in derivation (ρ=0.87, P<0.001) and validation (ρ=0.82, P<0.001) data sets. Using a cutoff of scores <9 to indicate dissatisfaction showed fair discrimination in derivation (sensitivity 85%, specificity 80%) and validation data sets (sensitivity 75%, specificity 78%). CONCLUSION: It is possible to quickly and efficiently assess satisfaction with follow-up clinics with three questions. This brief PROM could prove useful in monitoring services quality by allowing clinic users to provide timely feedback on their care.